Effects of atmospherically relevant PM2.5 on skeletal muscle mitochondria: a review of damage mechanisms and potential of exercise interventions - Ding, Yi; Wan, Qiliang; Liu, Wenduo (Frontiers in Public Health, 2025)
This study aims to explore the multifaceted impacts and mechanisms of fine particulate matter (PM2.5) exposure on skeletal muscle mitochondria. Evidence suggests that PM2.5 can penetrate the respiratory barrier and enter the circulatory system, spreading throughout the body and causing significant damage to the morphology, quantity, and function of skeletal muscle mitochondria. This is manifested by a decline in oxidative phosphorylation efficiency and mitochondrial dysfunction. Meanwhile, PM2.5 exposure induces excessive production of reactive oxygen species, triggering oxidative stress responses that impair mitochondrial dynamic regulation. This further disrupts the balance of glucose and lipid metabolism in skeletal muscle, exacerbating the development of metabolic diseases. The review underscores the systemic effects on skeletal muscle following mitochondrial dysfunction after PM2.5 exposure and the preventive and treatment potential of exercise.